2008
DOI: 10.1097/olq.0b013e3181644bc9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Validation of a Real-Time Polymerase Chain Reaction Detection of Neisseria gonorrheae porA Pseudogene Versus Culture Techniques

Abstract: The present porA pseudogene real-time PCR comprises a valuable supplement to the traditional culture techniques for diagnosis of N. gonorrheae, especially for samples from extragenital sites such as pharynx and rectum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 32 publications
2
21
0
4
Order By: Relevance
“…The low number of gonorrhea cases and the lack of large sexual networks may also suggest effective contact tracing, which is a main focus in Norway. Nevertheless, a previous study [25] and recent surveillance reports (unpublished data) have suggested that the culturebased diagnostics results in false-negative tests in Norway. This is especially true for rectal samples in MSM who practice exclusively receptive anal sex.…”
Section: Discussionmentioning
confidence: 99%
“…The low number of gonorrhea cases and the lack of large sexual networks may also suggest effective contact tracing, which is a main focus in Norway. Nevertheless, a previous study [25] and recent surveillance reports (unpublished data) have suggested that the culturebased diagnostics results in false-negative tests in Norway. This is especially true for rectal samples in MSM who practice exclusively receptive anal sex.…”
Section: Discussionmentioning
confidence: 99%
“…For elucidation of the spectinomycin resistance determinant, the full-length 16S rRNA gene (1,545 bp) was sequenced (51), which surprisingly revealed a wild-type gene. Consequently, the full-length rpsE gene (519 bp) was PCR amplified and sequenced with the primers 5S-F (5=-TGGCAAAACATGA AATTGAAG-3=) and 5S-R (5=-GCCATGGTTAACTCCCAAAA-3=), which were designed based on the genome sequence of the spectinomycin-susceptible gonococcal reference strain FA1090 (GenBank accession no.…”
Section: Figmentioning
confidence: 99%
“…This is Ͻ100%, as is expected given the lower sensitivity of culture compared to that of NAAT, which is demonstrated by our direct culture positivity rate of 82% and in previous studies (4,(18)(19)(20)(21)(22)(23). The lower success of deferred cultures compared to that of direct cultures can be explained by the decreased viability of N. gonorrhoeae over time.…”
Section: Discussionmentioning
confidence: 44%